Common Starting Points, Different Directions: Assimilation policies for 'Travelling families' in Norway, Sweden and Finland c. 1850–1900. Issue 1 (1st January 2017) - Ericsson, Martin
Abstract : In the late 19th century, political debates emerged in Sweden and Norway as well as in Finland concerning Travelling families– in this article defined as indigenous itinerant families whom the settled population pejoratively designated with terms such as 'tatere' (Norway), 'tattare' (Sweden) or 'zigenare' (Finland). In this article, these debates are compared, and the transfer of ideas and proposals between the three countries is analysed. It is argued that, on a local level, similar politics of 'territorial exclusion' were enacted in all three countries. This was, however, challenged by 'liberal social politics', a strategy aiming not at exclusion but at forced assimilation by means such as, for example, removing children from their parents. This strategy was proposed in all three countries, and socio-political agents were well aware of the debates in the neighbouring countries. But it was only in Norway that the most far-reaching proposals were realized. This is explained mainly by pointing at the way in which leading agents chose to act when trying to implement their proposals. The article also problematizes some conclusions drawn in earlier research, where the emergence of debates on Travelling families has been explained by pointing at the rise of ethnic nationalism. Instead, the article argues, the emergence of the so-called 'social question' in Western Europe in the 19th century should be considered as an at least equally important background factor.